The Influence of User-Generated Content Information Credibility and Information Adoption on Consumer Purchase Intention - Nurashikin, Nazer Mohamed; Norizan, Jaafar; Kartinah, Ayupp (Human Resource Management Academic Research Societ, 2023)
Influencer marketing is considered one of the most significant developments in the marketing industry. Influencers use short-form content production methods such as blogging and video blogging as a way for their followers to gain insights into their personal and everyday lives, as well as their experiences and ideas. The purpose of this study is to identify the influence of information credibility and information adoption on consumer purchase intention toward cosmetic products in Malaysia. The study’s unit of analysis is a woman who has prior experience watching YouTube videos on cosmetic product reviews. Structural Equation Modelling in IBM-SPSS-AMOS 24.0 was used to test the proposed hypotheses of the research. The results indicate that both information credibility and information adoption influence consumers’ purchase intention toward cosmetic products in Malaysia.